Structural Model Of Value Management In Green Construction - Roufechaei, Kamand Mohammadzadeh (2016)
Sustainable construction development would contribute to improve value performance by decreasing operation cost in long run, improving quality of outputs, reducing material consumption as well as mitigating in wastage of resources. However, due to high initial cost and long payback period clients are not interested in implementation of sustainability in construction development. In line with this, the integration of value management (VM) and sustainable construction (SC) has been introduced to focus more on client attitude. While the possibility of integrating sustainability with value management study has been theoretically proposed in the literature, it has not yet been widely put into practice around the world. As a result, the main objectives of this study shaped to assess the modeling of integration of value management and sustainable construction as well as to evaluate the relationship between integrated value management and sustainable construction with project value performance with mediating effect of client attitude.